2015
DOI: 10.1016/j.jacc.2014.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Clinical Consequences of Untreated Central Sleep Apnea in Heart Failure

Abstract: Central sleep apnea (CSA) is a highly prevalent, though often unrecognized, comorbidity in patients with heart failure (HF). Data from HF population studies suggest that it may present in 30% to 50% of HF patients. CSA is recognized as an important contributor to the progression of HF and to HF-related morbidity and mortality. Over the past 2 decades, an expanding body of research has begun to shed light on the pathophysiologic mechanisms of CSA. Armed with this growing knowledge base, the sleep, respiratory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 145 publications
0
85
0
12
Order By: Relevance
“…Patients with CSA have increased chemoresponsiveness that promotes hyperventilation and hypocapnia 10, 12, 13. A factor contributing to hyperventilation is pulmonary vagal irritant receptor stimulation by pulmonary venous congestion.…”
Section: Pathophysiology Of Sleep‐disordered Breathing and Medical Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with CSA have increased chemoresponsiveness that promotes hyperventilation and hypocapnia 10, 12, 13. A factor contributing to hyperventilation is pulmonary vagal irritant receptor stimulation by pulmonary venous congestion.…”
Section: Pathophysiology Of Sleep‐disordered Breathing and Medical Trmentioning
confidence: 99%
“…However, both OSA and CSA interfere with neurohumoral systems and thus may worsen CHF, for example, by increasing sympathetic and renin–angiotensin–aldosterone activity, both targets of CHF therapy. To date, there is a consensus to consider that the first step in the management plan for patients with SDB and CHF should be optimization of CHF treatment 12, 13, 14. Indeed, previous studies have reported that optimization of pharmacological therapy15, 16, 17, 18, 19, 20 and the use of non‐pharmacological methods21, 22 to treat CHF can lead to an improvement in SDB.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment options for CSA include medications, oxygen, positive airway pressure and neurostimulation of the phrenic nerve. [35] While a number of medications have been studied in small trials with acetazolamide and theophylline demonstrating some improvement in randomized trials, none are currently recommended due to lack of larger and longer term trials. [36] Oxygen has been used and improves symptoms in some studies, but no long term randomized trials have been completed.…”
Section: Treatment Options For Csamentioning
confidence: 99%
“…Patients with congestive heart failure (CHF) and systolic dysfunction have a high prevalence of sleep disorder breathing. [1][2][3][4][5][6][7] This is mainly in the form of Cheyne Stokes breathing and central sleep apnea (CSA). CSA is characterized by a dysregulated and insufficient drive for breathing during sleep, resulting in repetitive episodes of insufficient ventilation and inadequate gas exchange.…”
mentioning
confidence: 99%
“…1,3,4,11 In addition, several parameters of cardiac performance as well as neuroendocrine abnormalities associated with CHF have also shown an improvement with the use of these ventilatory devices. 2,4 This has resulted in an increasing use of these ventilator systems in patients with CHF and CSA.…”
mentioning
confidence: 99%